Diastereoselective heterogeneous catalytic hydrogenation of Baylis-Hillman adducts - Mateus, C. R.; Almeida, W. P.; Coelho, F. (Elsevier B.V., 2000)
We describe herein our results concerning a highly diastereoselective heterogeneous hydrogenation of Baylis-Hillman adducts obtained from aromatic aldehydes. The results obtained are complementary to those already described for homogeneous catalytic hydrogenation reactions. (C) 2000 Elsevier Science Ltd. All rights reserved.